Corporate Governance and Financial Performance: A Moderating Impact of Female Director - Bello, Umar; Hashidu, Adamu Danazumi; Abubakar, Ibrahim Abubakar; Lass, Ruth (Kashere Journal of Management Sciences, 2024)
This study is aimed at examining the moderating impact of Female on Board on corporate Governance and financial performance of Deposit Money Banks in Nigeria over a period of 10 years (2008 to 2017). The study employed the use of secondary data collected from annual reports and account of Deposit Money Banks listed in the Nigerian Stock Exchange. The study used panel data from (11) Deposit Money Banks in the Banking Industry which is analyzed using Correlation analysis and Ordinary Least Square-Moderated Multiple Regression (OLS-MMR). Results shows that only board composition is found to have significant impact on financial performance of DMBs in Nigeria, all other variables in the first model are not significantly related with financial performance. But on moderating the relationship with female director, board size, foreign directors and female directors are found to have significant impact on financial performance of Nigerian DMBs. The research concludes that female director had great impact on financial performance of DMBs in Nigeria. Thus, the study recommends that Nigerian Code of Corporate Governance to be amended to require listed firms to disclose, in their annual reports gender diversity of their boards